2015
DOI: 10.1021/acs.jpcc.5b05375
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Monoethanolamine Adsorption on Hydroxylated Cr2O3Surfaces

Abstract: The adsorption of monoethanolamine (MEA), a wellknown CO 2 capture amine, on the hydroxylated (0001)-Cr 2 O 3 surface was investigated by periodic density functional theory calculations and complementary ab initio molecular dynamics. Two different adsorption modes were investigated: adsorption of MEA above the hydroxylated surface and substitution of a surface water molecule by MEA. Several MEA coverages were studied from 0.25 to 1 monolayer. An atomistic thermodynamic approach was used to take into account th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In the formation of two different morphologies, both MEA and BGBE play an important role as complexing agents. The higher bulk density (1.01 g cm –3 ) and higher p K a value (9.5) of MEA enables its fast complexation with metal ions followed by hydrolysis , when compared to the slow complexation rate of the pectin-containing BGBE extract affected by low bulk density (0.89 g cm –3 ) and low p K a (3.4) values. Hence, the nanoflakes are deposited first on the surface of the FSSM substrate followed by the deposition of nanoparticles, which is taken to advantage in this work. The van der Waals force of attraction holds the nanoflake@nanoparticle heterostructure compactly, as shown in Scheme S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In the formation of two different morphologies, both MEA and BGBE play an important role as complexing agents. The higher bulk density (1.01 g cm –3 ) and higher p K a value (9.5) of MEA enables its fast complexation with metal ions followed by hydrolysis , when compared to the slow complexation rate of the pectin-containing BGBE extract affected by low bulk density (0.89 g cm –3 ) and low p K a (3.4) values. Hence, the nanoflakes are deposited first on the surface of the FSSM substrate followed by the deposition of nanoparticles, which is taken to advantage in this work. The van der Waals force of attraction holds the nanoflake@nanoparticle heterostructure compactly, as shown in Scheme S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 is one of the most studied metal oxides owing to the number of its applications, including heterogeneous catalysis, photoelectrolytic water splitting, solar cells, gas sensors, etc. , The high surface area, good thermal and mechanical stability, low cost, and good resistance in acidic and oxidative conditions make TiO 2 a potential candidate to study in the domain of surface science. , In view of the biological applications of TiO 2 -based implants, amino acids, especially glycine binding to TiO 2 surface, has been reported. Recently, Kapica-Kozar et al have shown the importance of TiO 2 modification with various amines for CO 2 capture in achieving higher adsorption capacity . Apart from TiO 2 studies reporting alkanolamines (AKAs) binding to hydroxylated Cr 2 O 3 , Al(100), Cu(100), and Al 2 O 3 are available in the literature; however, their performance toward CO 2 capture is not evaluated. Importantly, the majority of studies reported on reduced or oxidized TiO 2 (rutile, , anatase, and brookite) surface reveal that CO 2 adsorption prefers taking place in chemisorption mode. , In our earlier study, we have demonstrated the efficacy of amino acids as effective sorbents to capture CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Only Fe3O4 was found on the surface. From literature review [16], the adsorption of MEA on the hydroxylated Cr2O3 surface of steel inhibited the steel corrosion. The two mechanisms of MEA effect on reduction of steel corrosion were then proposed: the adsorption of MEA and the formations of protective layers at surface of A283 carbon steel.…”
Section: Resultsmentioning
confidence: 99%
“…This might have been due to MEA adsorption on the metal surface resulting in a protective film. Then, the rates of cathodic and anodic reactions decreased [15,16]. From Fig.…”
Section: Characterization Methodsmentioning
confidence: 99%